Loan Disbursement in Animal Husbandry with Reference to Agriculture Development Bank, Bagar, Pokhara - Gaudel, Yadav Sharma; Gautam, Yashoda (Economic Literature, 2016)
This article analyzes the loan disbursement pattern from Agriculture Development Bank, Bagar, Pokhara in the past 10 (FY 2060/61-FY 2069/70) years to find out the rate of growth of disbursal for loan and changes in interest rate in animal husbandry and its responses from the farmers in and around Pokhara. The data were based on the internal records of the bank during FY 2060/61 to FY 2069/70. Data show that during the study period (2060-2069), the highest total loan disbursement of ADBN, Bagar was 176.35 million in FY2064/65 and the lowest was 109.74 million in FY 2062/63. The highest loan disbursement in animal husbandry was 16.23 million (14.79%) in FY 2062/63 and the lowest was 2.57 million (21.60%) in FY 2060/61. The highest growth rate of loan disbursement in animal husbandry was 214.8% FY 2061/62. Similarly, the rate of interest for the loan in Animal husbandry was the highest in FY 2060/61 with 16% per annum and it reached its lowest point in FY 2065/66 at 11% per annum. The highest amount of principal collection was Rs. 189.27 thousand in FY 2062/63 and the lowest was Rs. 24.69 thousand in FY 2060/61. Farmers are facing the problem of bank loan procedure even though animal husbandry is getting attention of the farmers to increase their investment. However, the beginners of animal husbandry feel discouraged by the tough condition in loan procedure, which shows that the bank policies have not become farmers-friendly. Economic Literature Vol.12 2014: 1-7